PERDAGANGAN BILATERAL ANTARA INDONESIA DENGAN NEGARA-NEGARA PATNER DAGANG UTAMA DENGAN MENGGUNAKAN MODEL GRAVITASI - Sarwoko Sarwoko (Jurnal Ilmiah MTG, 2009)
This paper is made to provide a theoretical justification for using the gravity model in the analysis of bilateral trade and apply the generalized gravity model to analyse the Indonesia’s trade(non-oil and gas) with its main trading partners (twelve Countries) using the pooled data estimation technique. In the model, the bilateral trade is linear function of economic size of the country (GDP), GDP per capita, and geographical distance between recipient export countries and export country(Indonesia).The result show that the Indonesia’s trade (total trade or export, respectively) are positively determined by the the size of economies, GDP per capita of the partners and negatively determined by geographical distance between Indonesia and its the main trading patners. The GDP and GDP per capita of Indonesia has no effect on the Indonesia’s trade, even negative coefficients. It may be because an increase of Indonesian income is to spend to domestic products so that reduce Indonesia’s export. However, most variables of standardized gravity model were statistically significant on Indonesia’s trade.